An Investigation of the Severity, Causes, Impact and Actions Against Counterfeiting and Smuggling in Nigeria - Aregbeyen, Omo (Mediterranean Journal of Social Sciences, 2012)
This paper provides evidence-based information through survey that counterfeiting and smuggling are severeproblems to the manufacturing sector and the economy of Nigeria and with significant negative effects. The several factorsfacilitating the counterfeiting and smuggling activities and the subsisting initiatives against these illegal undertakings wereexplored. A major reason uncovered why these initiatives have not been effective in curtailing the menace of counterfeiting andsmuggling is the lack of coordination among stakeholders. The paper therefore concludes that to make success of the fightagainst counterfeiting and smuggling and their undesired effects on businesses and the economy requires an integratedapproach from stakeholders. Accordingly, a number of recommendations are proposed.